2003
DOI: 10.3354/meps262277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of three-spined stickleback Gasterosteus aculeatus on zooplankton and chl a in shallow, eutrophic, brackish lakes

Abstract: The 3-spined stickleback Gasterosteus aculeatus often dominates fish communities in eutrophic, brackish, north-temperate lakes where it is thought to contribute significantly to the low zooplankton biomass and low grazing pressure on phytoplankton. To elucidate its effect on zooplankton community structure and phytoplankton biomass (chl a), we conducted a 5.5 mo enclosure experiment with sticklebacks at different densities in high nutrient concentrations and a salinity of 2 psu. Increasing fish density (0 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
(39 reference statements)
3
31
0
2
Order By: Relevance
“…As indicated in previous studies (Winkler and Thiel 1993;Nilsson et al 2004), G. aculeatus is the dominant species in the fish assemblage of many Baltic inshore systems. Its high abundance found near the area of the ASEU experiment (Table 2) is also typical for other inshore systems (Williams and Delbeek 1989;Jakobsen et al 2003). Although Pungitius pungitius was found to be the second most abundant fish species on the investigated spawning bed, it was not observed feeding on herring spawn.…”
Section: Discussionmentioning
confidence: 87%
“…As indicated in previous studies (Winkler and Thiel 1993;Nilsson et al 2004), G. aculeatus is the dominant species in the fish assemblage of many Baltic inshore systems. Its high abundance found near the area of the ASEU experiment (Table 2) is also typical for other inshore systems (Williams and Delbeek 1989;Jakobsen et al 2003). Although Pungitius pungitius was found to be the second most abundant fish species on the investigated spawning bed, it was not observed feeding on herring spawn.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have shown that these species prey intensively on zooplankton (García-Berthou 1999Blanco et al 2003). According to experimental studies (Jakobsen et al 2003), fish densities above 4 to 6 stickleback m 22 can lead to substantial changes in the zooplankton community structure and may cause a shift from a clear to a turbid state in temperate brackish lakes. In our study, higher fish densities were found in Selbjerg, Ter Vell, Salins, and Sirvent Lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is also emerging evidence that fish communities may change along the salinity gradient (Jensen et al 2010). Recent studies have shown that eutrophic and hypertrophic brackish temperate lakes hold a fish community resembling that of warm lakes, that is, with dominance of small planktivorous fish, such as three-spined stickleback (Gasterosteus aculeatus) and nine-spined stickleback (Pungitius pungitius), which have more cohorts per year than fish in comparable freshwater lakes (Jeppesen et al 1994 and may predate intensively on the zooplankton (Jakobsen et al 2003). This would explain why nutrient-rich brackish lakes remain turbid even at high macrophyte coverage (Jeppesen et al 1994).…”
mentioning
confidence: 99%
“…The experiments were carried out from 3 May to 20 September 2000 in the slightly brackish (0.5 psu) Lake Kogleaks, located in the northern part of the nature reserve Vejlerne, Denmark. Eleven cylindrical, polyethylene enclosures (surface area ≈ 1 m 2 ) were fixed in and kept open to the sediment at a water depth between 70 and 80 cm (Jakobsen et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…To further elucidate the structuring role of planktivorous fish in eutrophic-hypereutrophic, shallow, brackish lakes, a mesocosm experiment adjusted to low salinity (2 psu) and a high nutrient level was conducted at contrasting densities of three-spined sticklebacks. In an earlier paper (Jakobsen et al 2003) we reported the effects on the zooplankton community; here, we describe changes in phytoplankton biovolume, composition and size.…”
Section: Introductionmentioning
confidence: 99%